Winter cover crops shape early‐season predator communities and trophic interactions - Carson Bowers; Michael D. Toews; Jason M. Schmidt (Ecosphere, 2021)
Abstract Despite the dynamic nature of annual cropping systems, few studies have investigated how the structure of predator communities and their interactions with prey corresponds with crop seasonality. Adding winter habitat, such as cover crops, improves soil health and likely contributes seasonal habitat availability for arthropod communities. Stable habitat may lead to functionally diverse predatory communities and their associated ecosystem services, such as biological control. Here, we estimated predatory community functional changes based on foraging traits determined by molecular gut–content analysis (MGCA) in response to winter cover crops (rye and crimson clover) in a cotton agroecosystem. Predators were collected from replicated 1‐ha experimental field plots during each major stage of crop development in 2017 and 2018, and MGCA was used to estimate predator roles and responses to cover crop treatments. Cotton planted into a rye cover crop residue promoted unique predator communities in the early and mid‐season as compared to no‐cover fields. Correspondingly, we observed dissimilar prey consumption among cover crop treatments. Winter cover crops led to an increase in consumption of alternative prey and incidental pests by natural enemies on seedling cotton and encouraged high predator diversity that aligns temporally with potential early‐season pest outbreaks. Therefore, cover crops commonly employed for soil health and erosion benefits also contribute to pest management by providing habitat and alternative prey resources that boost early‐season predatory arthropod communities.